Lateral behavior of monopiles considering the effects of sand subsidence and densification under lateral cyclic loading. Issue 12 (2nd December 2022) - Wang, Yang; Zhu, Mingxing; Gong, Weiming; Dai, Guoliang; Lu, Hongqian; Wang, Bochen
Abstract: The deformation characteristics (namely, subsidence and densification) of sandy soil surrounding piles under lateral cyclic loading has become a major research topic. The behavior of soil subsidence reduces the embedded depth of monopiles and increases the bending moment of the pile head, which causes reduction of the piles' lateral capacity. In contrast, soil densification results in stiffening effect, which can increase the lateral capacity of monopiles. In this study, first, the changes of pile-soil system parameters caused by subsidence and densification are quantified based on the mass conservation principle of the subsidence zone and densification region. Then, lateral responses of monopiles before and after cycling are investigated by American Petroleum Institute (API) p - y curve model. The effects of the subsidence dimensions, initial relative densities and densification region modes (Mode 1 and Mode 2) on the pile lateral responses are analyzed. Lastly, a simple framework is proposed to evaluate the pile lateral capacity after cycling. Salient findings of this study are: (i) The lateral capacity of monopiles increases with the increment of subsidence dimension; (ii) The effect of cyclic loading on the lateral capacity of monopiles gradually decreased with the increase of initial relative densities; (iii) The significant nonlinear relationship between improvement ratio of pile lateral capacity and subsidence dimension revealed that Mode 2 agreed better with the actual conditions compared with Mode 1.